Carbon VIX : A case of decarbonized SPACs - Dimic, Nebojsa; Tinoco, Mario Hernandez; Piljak, Vanja; Vulanovic, Milos (Elsevier, 2024)
The recent Carbon volatility index (Carbon VIX) by Fuchs, Stroebel, and Terstegge (2024) raises important questions regarding its impact on the financial performance of decarbonizing companies. We investigate the relationship between decarbonized SPACs and the Carbon VIX. While the Decarbonised SPAC Index does not exhibit a statistically significant linear relationship with the Carbon VIX, a regime-shifting approach indicates a positive association in low-volatility environments. Furthermore, carbon prices show a positive effect in low price regimes. We highlight the importance of considering regime shifts and non-linear effects when assessing the impact of volatility and price dynamics on decarbonized SPAC performance.
Keywords: Carbon price; Carbon VIX; Carbon volatility; Energy; SPACs; Special purpose acquisition company; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|